Validitas Metode Real Time PCR GeneXpert pada Suspek TB Paru BTA Negatif di RSUD Dr. Doris Sylvanus - Silvani Permatasari; Vani Vrenika; Florence Felicia; Malasinta Malasinta; Ria Eriani; Ni Putu Saraswati; Mery Irayanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Indonesia is one of the developing countries with high TB patients in the world. The most common detection used for TB diagnosis is sputum smear examination. Smear negative pulmonary TB still have a risk of infection and can develop into active. The GeneXpert molecular examination is a rapid diagnosis of TB by the real-time PCR method. The purpose of this study was to assess the validity of GeneXpert in smear-negative pulmonary TB compared to Lowenstein Jensen's culture. The design of this diagnostic test study is a cross-sectional study. The study was conducted on 40 people with smear-negative pulmonary TB suspect patients in Dr. Doris Sylvanus Regional Hospital. Sputum examination was performed with GeneXpert and compared with Lowenstein Jensen culture. The results of GeneXpert validity for diagnosing smear-negative pulmonary TB suspect are sensitivity 81.8%, specificity 96.5%, positive predictive value 90%, negative predictive value 93.3%, and accuracy 92.5%. It was concluded that GeneXpert has sensitivity, specificity, positive predictive value, negative predictive value, and high accuracy as a diagnostic tool in smear-negative pulmonary TB suspects.